Personnel as a Factor of Production in Development of Regional Tourism Economy – a Conceptual Paper - Aleksander Panasiuk (Journal of Entrepreneurship, Management and Innovation)

(untitled)
Tourism economy appears in every sphere of economy: production of goods and services, their division, exchange and consumption; it also occurs in the majority of the national economy branches that directly or indirectly deal with meeting tourist demand. The majority of economic processes in tourism sector are realized by direct tourism economy and its representatives, tourist entrepreneurs. Territorial self- government units and tourist organizations play a significant role in formation of economic processes in tourism sector on the regional and local levels. The classic economy distinguishes three basic production factors: labor, land and capital. In the modern approaches they are completed with the fourth that has different names. Beginning with technical and organizational progress which is a logic extension of coexistence and cooperation of three basic factors, ending with information and knowledge – treated as the most modern factors of production in the so-called new economy. In the totality of activities of tourism economy entities, a special role should be ascribed to the personnel, namely human potential of tourism economy entities.